2016
DOI: 10.1007/s12035-016-9795-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Fisetin Against Amyloid-Beta-Induced Cognitive/Synaptic Dysfunction, Neuroinflammation, and Neurodegeneration in Adult Mice

Abstract: Alzheimer's disease (AD) is a devastating and progressive neurodegenerative disease and is characterized pathologically by the accumulation of amyloid beta (Aβ) and the hyperphosphorylation of tau proteins in the brain. The deposition of Aβ aggregates triggers synaptic dysfunction, hyperphosphorylation of tau, and neurodegeneration, which lead to cognitive disorders. Here, we investigated the neuroprotective effect of fisetin in the Aβ mouse model of AD. Single intracerebroventricular injections of Aβ (3 μl/5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(103 citation statements)
references
References 69 publications
1
89
0
Order By: Relevance
“…It has been reported that the Akt/GSK-3β pathway plays a vital role in mediating neuroinflammation in the hippocampus, which likely contributes to obesity and diabetes in aging mice [51, 52]. We thus measured activation of Akt/GSK-3β signaling in the hippocampus by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the Akt/GSK-3β pathway plays a vital role in mediating neuroinflammation in the hippocampus, which likely contributes to obesity and diabetes in aging mice [51, 52]. We thus measured activation of Akt/GSK-3β signaling in the hippocampus by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As depicted in Figure 6a, the expression level of PSD-95 was significantly decreased in both the cortex and hippocampus of the HFD-fed group in comparison with the control group. A presynaptic protein marker (synaptosomal-associated protein 23 (SNAP-23) that plays a vital role in synaptic plasticity [59] was also analyzed through Western blot analysis. Consistent with the previous findings, the expression of (SNAP-23) in both the cortex and hippocampus was decreased in the HFD-fed group in comparison with the control group (Figure 6a).…”
Section: Hfd Induces Synaptic Dysfunction and Memory Impairment In Momentioning
confidence: 99%
“…Recently, many neurotoxic agents have been employed in experiments in order to explore cellular functions and dysfunctions (Kumar and Kumar, 2010; van der Star et al, 2012; Abbasi et al, 2013; Jiang et al, 2015; Parekh, 2015; Ahmad et al, 2017; Kim et al, 2017). Their correlation with pathological characteristics of diseases via the utilization of neurotoxic agent-induced models is a helpful way to screen and discover potential therapeutic drugs for NDDs.…”
Section: Introductionmentioning
confidence: 99%